Technique and Quality Translation of Idhafi in The Matan Hadits of Arba'in al-Nawawi - Faturrahman, Muhammad Irfan; Yoyo, Yoyo; Zaini, Abdul Razif (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
The accuracy of translation from the source language (SL) to the targeted language (TL) is not easy work. The translator should act as the connector between the writer of the work and the reader of the translation. The paper tries to analyses the translation of Arbai'n An-Nawawi by using the techniques offered by Molina Albir. This is a qualitative study that focuses on how the translator translated the Idhofi case in the Matan of Araba'in as the material object of this paper. Besides, the authors distributed questionnaires to assess the quality of the translation. The paper found that the translator uses 11 techniques that consist of 64 data of literal, 25 data of amplification, 21 data of borrowing, 12 data adaptation techniques, 6 data of compensation, 2 data of discursive creation, 2 data of reduction, 1 data of generalization, 1 data of modulation, and 1 data of transposition technique. Meanwhile, from the quality of the translation, it can be concluded that the compensation technique is much more acceptable, with 81% very accurate, 73% acceptable, and 77% rated high legibility. It is because the method helps the reader to understand the meaning, message, and goals to be conveyed.